HUBUNGAN PENGETAHUAN DAN SIKAP PENGASUHAN ORANG TUA DENGAN MODEL REWARD DAN PUNISHMENT TERHADAP PRESTASI ANAK USIA 3-5 TAHUN DI TK NURIS JEMBER - Nuning Dwi Merina; Megawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
Children's achievements are the result of learning obtained from formal and non-formal education. There are several factors that affect a child's achievement, namely internal and external factors of the environment, because the influence is very big for the child's personal development, while the family is the closest person and first teacher for a child, especially parental care includes parental knowledge and parental attitudes and school conditions . This study used a descriptive population research design initially 60 respondents using the Slovin formula obtained a sample of 52 parents who have children aged 3-5 years of taking sampling with probability sampling technique with a simple random sampling approach. Spearmen rank test results indicate that there is a relationship between knowledge and attitudes of parents with the child's achievement with p value 0.001 <0.005. Based on this research it can be interpreted that there is a relationship of knowledge and attitudes of parents to the achievements of children aged 3-5 years in kindergarten Nuris Jember. Suggestions for parents to better understand how to respond to learning achievement in children. As for the teacher to be more supportive of children's learning achievement by giving a positive attitude so that the child's achievement can increase